2021
DOI: 10.1002/essoar.10507417.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Arctic Ocean in CMIP6 models: Biases and projected changes in temperature and salinity

Abstract: The Arctic is an integral part of the climate system that has undergone dramatic changes in recent decades. This includes the so-called Arctic amplification, which refers to atmospheric temperature increase in the Arctic that is at least two times higher than global mean values (Serreze & Francis, 2006), and that is associated with a rapid decrease in sea ice area and volume (

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…First and foremost, we used only one realisation per model, which is known to introduce a sampling error as each different realisation simulates a different possible outcome of the chaotic climate system (Wang et al, 2022). However, past studies suggested intramodel biases to be quite small compared to inter-model biases (e.g., Zanowski et al, 2021;Khosravi et al, 2022;Wang et al, 2022). We used a bootstraping approach to estimate those sampling errors and found this to be true for for most variables in our study.…”
Section: Summary and Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…First and foremost, we used only one realisation per model, which is known to introduce a sampling error as each different realisation simulates a different possible outcome of the chaotic climate system (Wang et al, 2022). However, past studies suggested intramodel biases to be quite small compared to inter-model biases (e.g., Zanowski et al, 2021;Khosravi et al, 2022;Wang et al, 2022). We used a bootstraping approach to estimate those sampling errors and found this to be true for for most variables in our study.…”
Section: Summary and Discussionmentioning
confidence: 87%
“…However, due to the harsh environmental conditions and sheer remoteness, measurements in the polar regions are relatively sparse (Khosravi et al, 2022), complicating especially ocean and sea ice diagnostics. Satellite observations help in the quantification of surface properties, however in-situ data to assess subsurface properties, like vertically resolved temperatures in the ocean, are limited.…”
Section: Introductionmentioning
confidence: 99%